Analysis of Shallot Growth and Production With Organic Fertilizer and Zeolite in Beach Sand Media - Rahmawati, Nini; Ladewa, Ibnu (Agrosains : Jurnal Penelitian Agronomi, 2023)
Shallots are a horticultural commodity that is cultivated intensively by farmers. Efforts to increase shallot production are carried out through extensification of sand around the coast, which is marginal land. The addition of organic fertilizer and zeolite as a soil conditioner is one effort to increase the productivity of sandy land. This research aims to analyze the growth and production of shallots cultivated in sand media using organic fertilizer and zeolite. The research was carried out in the greenhouse of the Faculty of Agriculture, University of North Sumatra, Medan from December 2021 to April 2022. This research used a randomized block design with 2 factors, namely the first factor was the type of organic fertilizer (without organic fertilizer). fertilizer). , cow dung, chicken dung and goat dung). ), the second factor is the zeolite dose (without zeolite application 7.5 tons/ha, 15 tons/ha and 22.5 tons/ha). The results of the research showed that the application of chicken manure had the best effect on increasing the growth and production of shallots, namely the variables observed were plant length, number of leaves, shoot dry weight, root dry weight, number of bulbs, bulb dry weight, and harvest index. The application of zeolite at a dose of 15 tons/ha increases the best growth and production of shallots which has a significant effect on plant length, number of leaves, and root dry weight and tuber dry weight. The interaction between organic fertilizer and zeolite did not have a significant effect on shallot productivity in sand media.